Застосування фітобактеріальних угруповань для біоремедіації екосистем (за матеріалами наукового повідомлення на засіданні Президії НАН України 27 грудня 2023 р.) - Гаврилюк, О.А. (Вісник НАН України, 2024)
Доповідь присвячено дослідженню шляхів взаємодії мікроорганізмів та
рослин з металами (іммобілізація і мобілізація) на прикладі Купруму та
можливості росту мікроорганізмів в умовах надвисоких концентрацій (до
1 моль/л) токсикантів. Теоретично обґрунтовано та експериментально
підтверджено ефективність застосування фітобактеріальних угруповань (мікроорганізмів та рослин) для біоремедіації екосистем. Currently, the most powerful source of metal pollution is the hostilities taking place on the territory of Ukraine as a result
of Russia’s full-scale invasion. Rocket, artillery and mortar attacks, as well as the activity of military equipment and
aviation led to the accumulation of heavy metals in the soil and the degradation of agrocenoses. The development of effective
methods of metals removal from polluted ecosystems is an urgent task of science and industry. The report deals
with study of the concept of thermodynamic prognosis of the interaction of microorganisms and plants with metal compounds,
microbial immobilization and mobilization of metals on the example of copper, accumulation of metals by phytoremediant
plants and their anaerobic degradation with energy carriers production. The approach is based on the thermodynamic
prognosis to substantiate the optimal pathway of microorganisms and plants interaction with metals. Thermodynamic
prognosis was used to determine the conditions and products of the interaction of microorganisms and plants
with metal compounds. According to the thermodynamic prognosis the types of interaction of microorganisms with
metals (on the example of copper) were clarified. Microorganisms were able to accumulate Cu2+ in microbial cells as a
result of replacing the macroelement Mg2+ (stereochemical analogy of metals and macroelements), precipitate copper
compounds without changing their valence state, and reduce Cu2+ to the insoluble oxide of monovalent copper Cu2O↓.
The postulates of the thermodynamic prognosis were experimentally confirmed in laboratory conditions. Bacteria resistant
to soluble Cu(II) compounds were isolated at the Department of Biology of Extremophilic Microorganisms of the
D.K. Zabolotny Institute of Microbiology and Virology of the National Academy of Sciences of Ukraine. They were not
only resistant to metals, but also interacted with them — accumulated in cells and reduced to insoluble and non-toxic
oxide Cu2O↓. Pseudomonas lactis UKR1 copper-resistant strain was studied. Strain was able to immobilize and mobilize
copper compounds under the regulation of microbial metabolism. According to the thermodynamic prognosis, the most
effective immobilization of metals should occur through reduction under conditions of significant difference between the
donor (microorganisms) and acceptor (metal-oxidizer) systems. As a result, the most effective reduction of metals should
be carried out by low-potential strict anaerobic microorganisms. This assumption was experimentally confirmed on the
example of methanogenic microbial community. It was shown that the methanogenic microbial community completely
(with 100% efficiency) immobilized copper during the anaerobic degradation of invasive plants biomass (water lettuce).
The high efficiency of microbial degradation of phytoremediant plant biomass (grasses, tobacco, wormwood, nettle, ragweed,
and goldenrod) with biogas synthesis has already been demonstrated at the Department of Biology of Extremophilic
Microorganisms. Thus, the availability of development of combined environmental biotechnologies of bioremediation
and phytoremediation of polluted ecosystems with simultaneous production of energy carriers — hydrogen and
methane was theoretically substantiated and experimentally confirmed.